Analisis Kaidah Jurnalistik pada Situs Berita Suara.com - Ni Putu Yunita Anggreswari; Geovani Ika Pranata Puteri (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
The high number of internet users in Indonesia has led to many shifts in effort to obtain information. This triggered the emergence of online media portals which then shifted the existence of newspaper which at the same time triggered the emergence of various online news sites. The challenge for online news portals is to research, where many of the online news stories feature clickbait headline in order to get more pageviews to read news that is presented. Clickbait headline is an online media effort to increase visitor traffic of pageviews. The competition that occurs in increasing pageview or the number of visits to online news sites is often carried out without heeding applicable journalistic principles. This triggered researchers to conduct more in depth research related to journalistic principles on the Suara.Com news site. This study used a qualitative descriptive research method using three data collection techniques including interview, observation and documentation technique. The result of this study are that the Suara.Com news site meets the rules of journalistic elements in term of making provocative news titles and fulfils the function of mass media, namely informative.